Complete response to immunotherapy in a nonagenarian patient with metastatic melanoma. Issue 7 (22nd July 2020) - Foo, Tiffany; Tapia Rico, Gonzalo; Brown, Michael P
Abstract : Despite the increasing incidence of metastatic melanoma in the older population, there are relatively limited data for those older than 75 years of age. Elderly patients are often under-represented in clinical trials. In addition, elderly patients in trials often have a lower Eastern Cooperative Oncology Group score and fewer comorbidities and may thus not truly reflect the realities of day-to-day clinical practice. We present a case of a 95-year-old woman who had extensive and unresectable subcutaneous and dermal deposits of metastatic melanoma of her right leg, which caused oedema and reduced mobility. She was treated concurrently with pembrolizumab and radiotherapy to her leg lesions of melanoma. She has had an excellent response to treatment, with complete resolution of the subcutaneous and dermal metastatic deposits and has not developed any immune-related toxicities. Our experience demonstrates that anti-programmed-death-receptor-1 therapy can be given safely and effectively even in very elderly metastatic melanoma patients.